1985
DOI: 10.3382/ps.0641050
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early Maturation of Brown Egg-Type Pullets, Flock Uniformity, Layer Protein Level, and Cage Design on Egg Production, Egg Size, and Egg Quality

Abstract: Eight-week-old Harco Sex-Link pullets were assigned to four growing regimens. Feed was restricted to Group 1. The birds reached an average weight of 1.52 kg at 20 weeks of age and were then light stimulated. Group 2 received the same ration ad lib and reached an average weight of 1.64 kg at 16 weeks. At this age they were light stimulated. Birds in Groups 3 and 4 were separated into two weight classes at 8 weeks of age. Those below the median weight received an 18% protein grower ration and those above the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Also, after selection for age at sexual maturity, it has correlated response on egg production traits. Concerning the effect of breed on age at sexual maturity, Kiling et al (1985) reported that early-matured pullets laid their first egg before 136 days, while late-matured pullets when they were 152 days of age. Egg production traits such as egg number, egg weight, egg mass and body weight at sexual maturity are affected by age at sexual maturity in chickens and quails (El-Bodgady et al 1993;Camci et al, 2002).…”
Section: Performance During Production Phasementioning
confidence: 99%
“…Also, after selection for age at sexual maturity, it has correlated response on egg production traits. Concerning the effect of breed on age at sexual maturity, Kiling et al (1985) reported that early-matured pullets laid their first egg before 136 days, while late-matured pullets when they were 152 days of age. Egg production traits such as egg number, egg weight, egg mass and body weight at sexual maturity are affected by age at sexual maturity in chickens and quails (El-Bodgady et al 1993;Camci et al, 2002).…”
Section: Performance During Production Phasementioning
confidence: 99%
“…As current genetic strains mature earlier (Arthur, 1985), the age at sexual maturity for optimum egg mass may be earlier than indicated by his analysis. Recent attempts to force earlier sexual maturity have been unsuccessful, even though pullets reached recommended body weights (Kling et al, 1985a(Kling et al, , 1985bLeeson andSummers, 1981, 1985). Kuney (1982, 1984) found no significant difference in egg income over feed cost when a stimulatory photoschedule was imposed at 18,20 or 22 weeks of age.…”
mentioning
confidence: 99%